Factors associated with adaptation level in the older adult residential care facilities: a path analysis - Zhao, Di; Niu, Meilan; Zhang, Shanfeng; Shi, Yan; Zhou, Lin; Song, Yuxia; Ma, Rui; Wang, Peng (Frontiers in Public Health, 2023)
Background：It has become very common for older adults to relocate to residential care facilities. whether older adults adapt to life in a long-term care residential facility through perception, reflection, and conscious behavioral choices is a challenging social issue. Few studies have formally examined bivariate relationships between these factors, and the influence of adaptation between these factors internally remains unclear. Therefore, there is a need to examine the structural causality of adaptation in residential care facilities influenced by a combination of physical, emotional, social and psychological factors, life satisfaction, and social support. Methods: The present cross-sectional study recruited older adults from three residential care facilities in Henan province, China, through convenience sampling. The Chinese Nursing Home Adjustment Scale (NHAS), Geriatric Depression Scale-15 (GDS-15) and Social Support Scale (SSRS), Satisfaction with Life Scale (SWLS), and Barthel Index were employed to measure the elderly’ adjustment level, depression level, social support, satisfaction with life, and self-care ability of the elderly, respectively. Results: A total of 210 participants completed the questionnaire. The model demonstrated an acceptable fit of the data. The results showed that the difference between life satisfaction and depression on the level of adaptation was 60% and 23%, respectively. Social support and life satisfaction had a positive direct effect on the level of adaptation, both showing a positive correlation with the level of adaptation. Depression, on the other hand, have a direct effect on the level of adaptation and showed a negative correlation with the level of adaptation. Conclusions: Social support has a positive impact on both life satisfaction and depression, which in turn promotes adaptation. As a major source of social support, family members and nursing home staff in residential care facilities can enhance social support for older people through improved interaction, which can have a meaningful and positive impact on levels of adjustment. The model demonstrates the strengthening and weakening of social support, self-care, life satisfaction, and depression levels, which can help inform the development of relevant care health strategies for older people to promote levels of adjustment and improve quality of life.